THE IMPACT OF CLASSICAL MASSAGE ON SPINE MOBILITY - Agnieszka Radzimińska; Magdalena Weber-Rajek; Ewelina Lulińska-Kuklik; Paulina Piecka; Waldemar Moska (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Introduction. Irregularities in movable property of the spine affect a large part of society and the problem affects the people at an increasingly younger age. Classical massage is a form of mechanotherapy that affects the regulation of the work of muscles, joints, tendons and ligaments. Aim of work: The purpose of this study was to evaluate the efficacy of classical massage section of thoracolumbar spine to increase the mobility in these segments. Material: The study was carried out on 36 healthy volunteers (20 women and 16 men) aged 21 to 27 years old (average age - 23.8) who were subjected to a series of five classical massages (according to strictly established protocol). In order to objectify the effects in all subjects before and after a series of treatments the following measurements were made: the fingers-floor test; the Otto -Wurna test; the straightening of the spine; lateral flexion of the spine; twist of the spine. Results A statistically important difference has been shown in the results of all tested variables before the first and after the last treatment of classical massage. Conclusions The results of personal research apply to young, healthy volunteers. It is worth to continue research into the effects of this form of therapy in the case of restrictions of movable tangible property, resulting from spinal pain syndromes.